Pemanfaatan Potensi Kelapa Sawit Hasil Replanting untuk Pembuatan Gula Merah (Arenga Pinnata Merr) di PT. Barumun Agro Sentosa - Ayu Afifah Sihombing; Sri Dewi Harahap; Epa Saulina Siregar; Arifky Manahan Simamora; Edi Gunawan Harahap; Raja Aminuddin Siregar (Jurnal Pengabdian, 2025)
The replanting process in plantation sectors generates significant biomass waste that is often underutilized. This study aimed to valorize felled trunks from replanting activities into a value-added food commodity at PT. Barumun Agro Sentosa. The method employed was participatory action research, comprising field observations, interviews, and production demonstration plots conducted in September 2025. Sap collection was performed using the apical meristem tapping technique on felled trunks aged approximately 25 years. To ensure quality and prevent fermentation, the sap acidity was maintained at a pH of 6.0 to 7.0 using natural preservatives before undergoing thermal evaporation. The results indicated that the average sap productivity ranged from 1.7 to 2.5 liters per trunk per day. The final product exhibited a solid texture, dark color, and distinctive savory-sweet taste comparable to traditional palm sweeteners. It is concluded that processing sap from felled trunks is technically feasible and supports the concept of zero waste agriculture. This practice offers a viable economic alternative for local communities and plantation workers by transforming residue into profitable resources.